IgG4-Related Inflammatory Pseudotumor Involving the Clivus: A Case Report and Literature Review - Liu, Xiaohai; Wang, Renzhi; Li, Mingchu; Chen, Ge (Frontiers in Endocrinology, 2021)
IgG4-related inflammatory pseudotumors are very uncommon and are characterized histologically by the presence of inflammatory swellings with increasing IgG4-positive plasma cells and lymphocytes infiltrating the tissues. As reports of intracranial IgG4-related pseudotumors are very rare, we report a case of an IgG4-related inflammatory pseudotumor involving the clivus mimicking meningioma. A 46-year-old male presented with intermittent headache for 2 years and a sudden onset of dysphagia and dysphonia of 7 days’ duration along with lower limb weakness. Enhanced magnetic resonance imaging (MRI) of the skull base revealed an isointense signal on T1- and T2-weighted images from an enhanced mass located at the middle of the upper clivus region, for which a meningioma was highly suspected. Then, an endoscopic transsphenoidal approach was adopted and the lesion was partially resected, as the subdural extra-axial lesion was found to be very tough and firm, exhibiting fibrous scarring attaching to the brain stem and basal artery. After the surgery, brain stem and posterior cranial nerve decompression was achieved, and the patient’s symptoms, such as dysphagia, dysphonia and lower limb weakness, improved. Pathological findings showed many IgG4-positive plasma cells and lymphocytes surrounded by collagen-rich fibers. The patient was sent to the rheumatology department for further glucocorticoids after the diagnosis of an IgG4-related inflammatory pseudotumor was made. This case highlights the importance of considering IgG4-related inflammatory pseudotumors as a differential diagnosis in patients with lesions involving the clivus presenting with a sudden onset of symptoms of dysphagia and dysphonia along with lower limb weakness when other more threatening causes have been excluded. IgG4-related inflammatory pseudotumors are etiologically enigmatic and unpredictable, and total resection might not be warranted. Glucocorticoids are usually the first line of treatment after diagnosis.